The Influence of Product Price, Outlet Location, and Discounts on the Interest to Rebuy - Sinurat, Andrio Avelino; Simanjorang, Elida Florentina Sinaga; Zebua, Yuniman (Almana : Jurnal Manajemen dan Bisnis, 2024)
Product prices, outlet locations, and discounts are several important factors in influencing consumer repurchase intentions. Reasonable and affordable prices can encourage consumers to buy products again. Strategic and easily accessible sales locations can also increase consumer interest in repurchasing a product. The discount at a lower price will broaden consumer interest to make repeat purchases. This study aims to describe and test how much influence partially and simultaneously the price, outlet location, and discount variables have on repurchasing interest for popcorn snacks in the city of Rantauprapat. This type of research is quantitative descriptive research with 100 respondents. The results of the research show that partially the price, outlet location, and environment variables have a positive and significant effect on the intention to repurchase popcorn snacks. The location of popcorn sales outlets that are easy to reach and easy to find is the most dominant reason for a consumer to make a repeat purchase, then the price is competitive according to taste and followed by a discount for purchasing a certain amount. Simultaneously it also shows that price, location, and discount have a positive and significant effect on the intention to repurchase popcorn in the city of Rantauprapat.